Twenty years of the International Society for Pediatric and Adolescent Diabetes Science Schools programs: Assessment of their impact on the participants' personal careers and networking development. - Dos Santos, Tiago Jeronimo; Chobot, Agata; Laimon, Wafaa; Waldron, Sheridan; Piona, Claudia; Giani, Elisa; Dovc, Klemen; Macedoni, Maddalena; Mameli, Chiara; Cardona‐Hernandez, Roque; Aschemeier‐Fuchs, Bärbel; McGill, Margaret; et al. (Pediatric Diabetes, 2022)
Objective: The following report describes the evaluation of the ISPAD Science School for Physicians (ISSP) and for Healthcare Professionals (ISSHP) in terms of their efficiency and success. Methods: All past attendees from 2000–2019 ISSP and 2004–2019 ISSHP programs were invited to respond to an online survey to assess perceived outcomes of the programs on career development, scientific enhancement, scientific networking, and social opportunities. Results: One‐third of the past ISSP (129/428), and approximately 43% of the past ISSHP attendees (105/245) responded to the surveys. Most of ISSP attendees reported that the programs supported their career (82%) by helping to achieve a research position (59%), being engaged with diabetes care (68%) or research (63%) or starting a research fellowship (59%). Responders indicated that ISSP was effective in increasing interest in diabetes research (87%) and enhancing the number (66%) and quality (83%) of scientific productions, and promotion of international collaborations (86%). After the ISSP, 34% of responders received research grants. From the first round of the ISSHP survey (2004–2013), responders reported have improved knowledge (60%), gained more confidence in research (69%), undertaken a research project (63%), and achieved a higher academic degree (27%). From the second round (2014–2019), participants indicated that the program was valuable/useful in workplace (94%) through understanding (89%) and conducting (68%) research and establishing communication from other participants (64%) or from faculty (42%). After the ISSHP, 17% had received awards. Conclusions: From the participants' viewpoint, both programs were effective in improving engagement with diabetes research, supporting career opportunities, increasing scientific skills, and enhancing networking and research activities.